L’insularité aujourd’hui : entre mythes et réalités - Thierry Nicolas (Études Caribéennes)
Numerous studies in various fields (economics, statistics, geography, etc.), have attempted to define the constraints posed by geographic reality on the economic success of the islands. For the most part, these studies present insularity as a handicap difficult to overcome (limited territorial extent, sparse population, higher costs, etc.). Nevertheless the development prospects of these territories permanently isolated by the sea, with reduced opportunities in terms of space, natural resources or human, or market size, are not necessarily doomed to failure